Ethiopia : Accounting and Auditing - World Bank (World Bank, Washington, DC, 2013)
This Report on Observance of Standards and Codes (ROSC) provides a review of the accounting and auditing practices and the institutions underpinning the accounting and auditing environment in the corporate sector in Ethiopia. The review drew on best international practices and makes policy recommendations aimed at improving the quality of financial reporting in the country. There are some notable efforts in Ethiopia aimed at improving the quality of financial information. One is aimed at establishing accounting and auditing standards for the private sector under the auspices of the Office of the Federal Auditor General (OFAG). Another is aimed at improving the capacity for public finance management under the auspices of the Ethiopian Civil Service College (ECSC). Work is also ongoing on revision of the Ethiopian Commercial Code under the auspices of the Ministry of Justice. The aim of this ROSC has been to complement the existing efforts by producing a holistic evaluation of all necessary pillars for a strong financial reporting infrastructure. While this report focuses mainly on corporate sector accounting and auditing, it also recognizes the need to ensure a well coordinated Commercial Code under the auspices of the Ministry of Justice. The aim of this ROSC has been to complement the existing efforts by producing a holistic evaluation of all necessary pillars for a strong financial reporting infrastructure. While this report focuses mainly on corporate sector accounting and auditing, it also recognizes the need to ensure a well coordinated approach to develop (i) accounting and auditing standards; and (ii) education and training systems in accounting and auditing, in the public and private sectors.